Can AI Detect Cancer Earlier Than Traditional Screening Methods? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2020)
The early detection of cancer is a cornerstone of effective treatment and improved patient outcomes. For decades, traditional screening methods such as mammo...
Keywords: AI in Medical Imaging and Diagnostics; Detect; Cancer; Earlier; Artificial Intelligence; Machine Learning; Deep Learning